(3GSJQGJjLjI GdGYeGd (B:s (3eONd JWHjbj (B/s - (3GdZGdHj, WGgQs; (3GdYHGOj, hGKb s ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2006)
(3ebOeI aj GdGOGQI GdGSJQGJjLjI GVGaI Gdi GceGd GdNWI GdGSJQGJjLjI (B,(3GjUGd GdNWI GdGSJQGJjLjI(B, (3JfajP GdNWI GdGSJQGJjLjIhcPG GdbjGS GdGSJQGJjLj(B, (3GdYhOI Edi GdNWI GdGSJQGJjLjI h aj GdGNjQ WQM HYV GdMGdGJ GdOQGSjI (B( (3MGdI TQcI GdWjQGf (B, (3GMGdI eSJTai GdNOeGJ GdHjWQjI(B).s
(3GdeQGLY U(B.151, (3edGMb U(B.147s
Keywords: (3GOGQI GdGYeGds